EVALUATION OF THE EFFICACY OF BELSAP HYDROGELS ON GROWTH AND YIELD OF SELECTED WHEAT VARIETIES IN MARGINAL AREAS OF NAROK COUNTY - Marete, Bundi; Mutinda Komu, Joseph; Kamau, Peter; Mushimiyimana, David (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
Wheat (Triticum aestivum L.) is one of the most important cereal crops in the world. According to Food and Agricultural Organization, wheat accounts for 31.4% of world cereal production and 31.5% of the total quantity of cereals traded. In Kenya, it is the second most important cereal crop after maize. To increase domestic wheat production, there is need to introduce efficient technologies as well as price and market incentives. The objective of the study was to evaluate the efficacy of Belsap hydrogels on growth and yield of selected wheat varieties in marginal areas of Narok County. Three wheat varieties (Eagle 10, Kingbird, Durra 1) and four treatments (Belsap+DAP, Belsap, DAP and Control) were applied as a replicated trial in a randomized complete block design. From the results, there were statistically significant differences between treatment means (p<0.05) for stand count, plot vigour, plant height, grain weight, number of tillers per plant, days to 50% physiological maturity, total biomass, yield and harvest index. Among the varieties, there were statistically significant differences (p<0.05) for 1000 grain weight, days to 50% physiological maturity, grain yield and harvest index. There were no significant differences for variety means for stand count, plant height, vigour, and number of tillers. Experimental plots under Belsap+DAP treatment recorded the highest performance followed by DAP, Belsap and Control. Eagle 10 variety had the best performance followed by Kingbird and Durra 1.